2022
DOI: 10.1136/jitc-2022-004585
|View full text |Cite
|
Sign up to set email alerts
|

IL1R2 increases regulatory T cell population in the tumor microenvironment by enhancing MHC-II expression on cancer-associated fibroblasts

Abstract: BackgroundRegulatory T cells (Treg) are an integral part of the tumor immune tolerance. Carcinoma-associated fibroblasts (CAFs) is a pivotal driver for accumulation of Treg cells in the tumor microenvironment (TME). The molecular nature underpinning Treg cells and CAFs coupling needs to be further defined.MethodsThe Il1r2flox/floxFoxp3Cre mice were generated to establish the conditional knock-out of Il1r2 in Foxp3+ Tregs in vivo. Using the MC38 tumor model, we evaluated the antitumor efficacy of immune checkpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In addition to newly developing tTregs, the thymus also contains mature, highly activated Tregs, labeled as rrTregs, which are thought to have recirculated from the periphery 74,75 . These rrTregs do not express CCR7 or thymic egress markers (KLF2, S1PR1), but do express IL1R2 (Sup Figure 5F), a receptor known to sequester the inflammatory cytokine IL-1 to reduce local concentrations 76 . CODEX imaging identified tTregs and rrTregs dispersed throughout the medulla, with rrTregs primarily adjacent to DCs marked by CD68 expression (Figure 5G).…”
Section: Spatial Multiomics Reveals Key Mechanisms Regulating Negativ...mentioning
confidence: 99%
“…In addition to newly developing tTregs, the thymus also contains mature, highly activated Tregs, labeled as rrTregs, which are thought to have recirculated from the periphery 74,75 . These rrTregs do not express CCR7 or thymic egress markers (KLF2, S1PR1), but do express IL1R2 (Sup Figure 5F), a receptor known to sequester the inflammatory cytokine IL-1 to reduce local concentrations 76 . CODEX imaging identified tTregs and rrTregs dispersed throughout the medulla, with rrTregs primarily adjacent to DCs marked by CD68 expression (Figure 5G).…”
Section: Spatial Multiomics Reveals Key Mechanisms Regulating Negativ...mentioning
confidence: 99%
“…A recent study shows evidence that Tregs can also modulate the phenotype of CAFs in an IL-1 signalling-dependent manner [ 59 ]. The authors show that IL-1R2, a decoy receptor for IL-1β, is exclusively expressed by tumour-infiltrating Tregs in several murine and human cancer types.…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…Inhibition of IL-1β signalling in CAFs results in increased expression of MHC-class II, indicating that the presence IL-1R2 + -Tregs in the TME can drive the differentiation of apCAFs, which the authors further describe, promoting the additional accumulation of Tregs. Supporting this, specific blockade of IL-1R2 in Tregs in their murine models improved anti-tumour immunity upon ICI therapy in several murine models [ 59 ].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…3F, G and 4A). 31 FOXP3, a key transcription factor in Tregs, plays a crucial role in their differentiation, maturation, and in vivo inhibitory activity. 32,33 We found that the expression of Foxp3 was down-regulated after anti-TIGIT treatment (Fig.…”
Section: Landscape Of Cd45 + Cells In Mc38 Tumorbearing Mouse Modelmentioning
confidence: 99%